Load Distribution Factors for Horizontally Curved Concrete Box Girder Bridges - Eyad K. Sayhood; Raid I. Khalel; Hashim M. Hassan (Engineering and Technology Journal, 2014)
In this study, a 3-D finite element model was used for the analysis of the horizontally curved bridge slab built monolithically with box girders. A parametric study was carried out to calculate the load distribution factors for horizontally curved reinforced concrete box girder bridges based on (AASHTO 1996) live loads by using F.E.M by SAP 2000 (Structural Analysis Program). The parameters considered in this study were: span-to-radius curvature ratio, span length, number of longitudinal girders, girder spacing and number of lanes. The analysis of the bridge was done for the case of full live loads and partial live loads.